Decrypting the feared genus Hiatella (Bivalvia): South American species - Zelaya, Diego Gabriel; Güller, Marina (Zoological Journal of the Linnean Society)
Hiatella is among the most poorly understood bivalve genera. Most of the species remain known only from shell morphology, which has proved to be extremely variable in the group. Few studies have addressed their anatomy and biology, and no studies have combined morphological, anatomical and biological characters with molecular characters. This has led to the hiatellids all around the world being regarded as a single, widely distributed species. This contribution represents a step towards a better understanding of hiatellids worldwide by providing the first integrative study of the species occurring in southern South America. Three entities are recognized: Hiatella meridionalis, Hiatella barnea and Hiatella umbonata sp. nov. To understand their intraspecific variability, all the species are carefully described and figured, based on large series of specimens. Saxicava chilensis, Saxicava mollis, Saxicava lebruni and Saxicava subantarctica are considered synonyms of H. meridionalis; a lectotype for S. subantarctica is designated; and S. antarctica and S. frigida are regarded as nomina dubia. This study suggests that worldwide living hiatellids might have originated from South American species and that reduction/loss of hinge teeth during ontogeny and life on hard substrates or on/ inside other invertebrates would represent derived traits within the genus Hiatella. Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Güller, Marina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina